Designing the user interface strategies for effective human-computer interaction - Shneiderman, Ben; Cohen, Maxine (Maxine S.); Elmqvist, Niklas; Jacobs, Steven M.; Plaisant, Catherine (Pearson Education Limited, 2018)
'Designing the User Interface' provides a comprehensive, authoritative introduction to the dynamic field of human-computer interaction (HCI). Students and professionals learn practical principles and guidelines needed to develop high quality interface designs - ones that users can understand.